1998
DOI: 10.1136/jcp.51.4.324
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E alleles in women with severe pre-eclampsia.

Abstract: This study investigated the frequency of apolipoprotein E (apoE) alleles among women with severe pre-eclampsia. The presence of the three most common apoE alleles ( 2, 3, 4) was determined by polymerase chain reaction-restriction fragment length polymorphism in three groups of white women: non-pregnant healthy (n = 101), pregnant healthy (n = 52), and pregnant with a diagnosis of severe pre-eclampsia (n = 54). The frequency of apo 2 was highest among women with severe pre-eclampsia (16.6%) followed by non-preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 5 publications
1
23
0
2
Order By: Relevance
“…In the general population, the ε3 allele is most common (with a prevalence of over 60%), and E3 is the predominant circulating apoE variant. An association between the ε2 allele and preeclampsia was formerly suggested by Nagy et al (24), but this hypothesis was not confirmed in several following studies (25)(26)(27)(28). Moreover, Belo et al (26) reported no differences in the prevalence of the ε3 allele in a large cohort of pregnant women with respect to their pregnancy outcome (healthy or complicated by preeclampsia).…”
Section: Discussionmentioning
confidence: 89%
“…In the general population, the ε3 allele is most common (with a prevalence of over 60%), and E3 is the predominant circulating apoE variant. An association between the ε2 allele and preeclampsia was formerly suggested by Nagy et al (24), but this hypothesis was not confirmed in several following studies (25)(26)(27)(28). Moreover, Belo et al (26) reported no differences in the prevalence of the ε3 allele in a large cohort of pregnant women with respect to their pregnancy outcome (healthy or complicated by preeclampsia).…”
Section: Discussionmentioning
confidence: 89%
“…Increased plasma apoE polymorphisms have been reported in women with pre-eclampsia (17,18), however findings relating to apoA1 measurements in pre-eclampsia are conflicting (19,20). To-date, it is not known whether AIBP is expressed in the placenta or altered in pre-eclampsia.…”
Section: Introductionmentioning
confidence: 99%
“…The candidate genes reported to be associated with PIH are classified into four groups and include the blood pressure regulation system, metabolic system, coagulation and the fibrinolysis system, and immunity system groups (Table 2) [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. This classification is dependent upon the molecules and the factors might provide some benefits such as elevating the sensitivity for isolating susceptibility genes of PIH.…”
Section: Candidate Genes Of Eh and Pihmentioning
confidence: 99%